Business cycle and economic-wide energy intensity: The implications for energy conservation policy in Algeria. (August 2015) - Adom, Philip Kofi
Abstract: Despite the prevalence of voluntary and involuntary energy conservation policies, developing countries in Africa continue to struggle to achieve energy efficiency targets. Consequently, energy intensity levels have risen threatening the security of the energy system. This raises the important question: is there an economic state that induces agents to be energy conscious? In this study, we study the case of Algeria's energy intensity from 1971 to 2010. First, the paper argues that there is a certain economic state that economic agents find investing in energy conservation a viable option. Any state different from that would mean not investing in energy conservation. Second, the paper argues that the economy can do better even with an infinitesimal reduction in fuel subsidy, and that the gains in revenue from the policy can compensate for the negative socio-economic and equity impacts associated with such a policy. Third, the paper argues that, so long as, industrial expansion in the country move parallel with investment in technological innovation, long-term sustainable growth and energy conservation targets are jointly feasible. Fourth, the paper shows that income elasticity evolves with the business cycle, and the absorptive capability of the host country affects how FDI (foreign direct inflows) impact energy intensity. Highlights: Low income states inhibit fuel substitution and investment in energy conservation. Income elasticity evolves as we pass through boom and recessionary periods. The goals of sustainable growth and energy conservation are not mutually exclusive. Absorptive capability affects the impact of FDI on energy intensity.